Joint association of sleep duration and physical activity with cognitive performance among Chinese adults: an analysis of nationally representative survey data - Tao, Huan; Wang, Tao; Jia, Yong-Qian (Frontiers in Public Health, 2023)
Background: Although previous studies have identified that both physical activity and sleep problems are independently associated with decreased risk of cognitive function. However, the joint association of physical activity and sleep duration with cognitive function was rarely studied. Methods: A total of 21,128 participants who had records from the China Family Panel Studies (CFPS) in 2018 were included in this study. Linear regression was used to examine the associations of joint between physical activity and sleep duration with cognitive function in the nationally representative survey data. Results: Compared with individuals reporting 150 min/week or more of activity, those reporting no physical activity had a 116% higher risk of getting lower vocabulary scores (coefficient: -1.16, 95% CI: -1.55 -0.78) and a 61% higher risk of getting lower mathematics scores (coefficient: -0.61, 95% CI: -0.78 -0.44). Compared with those who slept for 7-10 h/day, those who slept more than 10h/day had the lower vocabulary scores (coefficient: -1.34, 95% CI: -1.86 -0.83) and mathematics scores (coefficient: - 0.68, -0.94 -0.42). The results of joint analysis showed that the adjusted coefficient for vocabulary scores were -2.58 (95% CI, -3.33 -1.82) for individuals reporting no physical activity and sleeping for 10 h/day, and -1.00 (95% CI, -1.88 -0.12) for individuals reporting more than 150 min/week and sleeping for 10 h/day, compared with those who reported a sleep duration for 7-10 h/day and more than 150 min/week physical activity, Any level of physical activity combined with longer sleep duration (≥ 10h/day) was associated with a higher risk of getting low mathematics scores. Conclusions: Appropriate sleep and sufficient physical activity together may have amplified association on cognitive performance, highlighting the importance of a comprehensive healthy lifestyle.